Tinjauan Hukum pada Tindak Pidana Melakukan Persetubuhan Terhadap Anak Dari Undang-Undang Nomor 35 Tahun 2014 - Mahalia Nola Pohan; Sri Hidayani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
Children are entrusted by the almighty as the next generation of this nation who must be protected from all kinds of criminal acts, including criminal acts of sexual abuse which is a cruel act that almost all of the world condemned the behavior. The problem in this study is the legal consequences of the crime of sexual abuse with children, the judge considered the decision No. 934 / Pid.Sus / 2016 / Pn.Mdn and the factors causing the crime to commit sexual abuse to children. The results and discussion in this study are legal consequences arising from criminal acts of sexual abuse to children is the birth of a legal relationship that gives rise to rights and obligations between countries, perpetrators and victims of criminal acts of sexual abuse to children based on the Law of the Republic of Indonesia Number 35 of 2014 concerning of Child Protection, the judge considers the decision No. 934 / Pid.Sus / 2016 / Pn.Mdn is to pay attention to matters that incriminate and alleviate, and consider the ability to be responsible, the judge accuse the defendant by considering Article 81 paragraph (2) of the Law Republic of Indonesia Number 35 of 2014 concerning Amendments to the Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection, the causes of criminal acts of sexual abuse to children are internal factors (low education and moral, psychological, and economic factors) and external factors (social culture, family and environment, technology, interaction and situation and the role of the victim.